Addressing child and adolescent obesity management in Ireland: identifying facilitators and barriers in clinical practice - Ferdous, Farzana; Arthurs, Niamh; Tully, Louise; O’Brien, Sarah; Smith, Susan M.; Walsh, Aisling; O’Gorman, Clodagh S.; O’Malley, Grace (Frontiers in Pediatrics, 2023)
Ireland's Model of Care for the Management of Overweight and Obesity outlines a plan for treating child and adolescent obesity (CO). However, engagement with key stakeholders is required to support implementation and improve health services.To map perceived barriers and facilitators related to CO management across healthcare settings, professional disciplines, and regions in the Republic of Ireland (ROI).This was an online cross-sectional survey of registered health professionals (HPs) designed to align with the Consolidated Framework for Implementation Research (CFIR), co-developed with a project team consisting of researchers, health professionals and patient advocates. The survey was pilot tested with project stakeholders and distributed online to professional groups and via a social media campaign, between September 2021 and May 2022, using 'SurveyMonkey'. Data were summarised using descriptive statistics and thematic analyses. Themes were mapped to the CFIR framework to identify the type of implementation gaps that exist for treating obesity within the current health and social care system.In total of 184 HPs completed the survey including nurses (18%), physicians (14%), health and social care professionals (HSCPs) (60%), and other HPs (8%). The majority were female (91%), 54% reported conducting growth monitoring with a third (32.6%) giving a diagnosis of paediatric/adolescent obesity as part of their clinical practice. Nearly half (49%) of the HPs reported having the resources needed for clinical assessment. However, 31.5% of HPs reported having enough 'time' and almost 10% of the HPs reported having no/limited access to suitable anthropometric measurement tools. Most HPs did not conduct obesity-related clinical assessments beyond growth assessment and 61% reported having no paediatric obesity training. CFIR mapping identified several facilitators and barriers including time for clinical encounters, suitable materials and equipment, adequate training, perceived professional competency and self-efficacy, human equality and child-centeredness, relative priorities, local attitudes, referral protocols, and long waiting times.The findings provide actionable information to guide implementation for the Model of Care for Managing Obesity in Ireland. Survey findings will now inform a qualitative study to explore implementation barriers and facilitators and prioritise actions to improve child and adolescent obesity management.